A qualitative exploration of doctors' and nurses' experiences on the management of tuberculosis and human immunodeficiency virus co-infection in a tuberculosis-human immunodeficiency virus high burden community in northern KwaZulu-Natal, South Africa - Mbuso Mabuza; Constance Shumba (AOSIS, 2018)
Background: South Africa is faced with a huge challenge of addressing the high burden of tuberculosis-human immune virus (TB-HIV) co-infection, and this challenge is more pronounced in the province of KwaZulu-Natal which has one of the highest burdens of TBHIV co-infection in the world. Aim: The study explored the experiences of doctors and nurses with regard to the management of tuberculosis and HIV co-infection in a TB-HIV high burden community in northern KwaZulu-Natal, South Africa. The particular focus was to provide insight and to inform policy and programme development for effective management of TB-HIV coinfection in the TB-HIV high burden community of northern KwaZulu-Natal. Methods: An interpretivist exploratory qualitative approach was employed through individual semi-structured interviews of 16 participants comprising eight doctors and eight nurses, with a total interview time of 8.95 hours. Purposive sampling was used to select the doctors and nurses from the public and private sector of the TB-HIV high burden community of northern KwaZulu-Natal. Thematic analysis was used to analyse the data. Results: Five key themes emerged from this study and these themes were discussed together with the sub-themes based on the various participant responses. The five key themes were practical experience about the management of TB-HIV co-infection; access to information and training on the management of TB-HIV co-infection; challenges and concerns about the management of TB-HIV co-infection; perception about local beliefs; and knowledge of policies and guidelines. Conclusion: Overall, this study highlights barriers that hamper the effective management of TB-HIV co-infection in northern KwaZulu-Natal. Recommendations of this study point towards an urgent need to scale up the management of TB-HIV co-infection through effective policies, improved capacity and infrastructure, stronger partnerships of all stakeholders, and further research.